MiR-451a and let-7i-5p loaded extracellular vesicles attenuate heme-induced inflammation in hiPSC-derived endothelial cells - Thomas, Justin J.; Harp, Keri Oxendine; Bashi, Alaijah; Hood, Joshua L.; Botchway, Felix; Wilson, Michael D.; Thompson, Winston E.; Stiles, Jonathan K.; Driss, Adel (Frontiers in Immunology, 2022)
Hemolysis is associated with many pathologies, including trauma, sepsis, hemorrhagic stroke, malaria, and genetic disorders such as sickle cell disease (SCD). When hemolysis occurs, free-heme drives vascular inflammation, resulting in oxidative tissue damage and cardiometabolic complications. A better understanding of heme clearance and detoxification is essential to preventing sustained tissue damage. Human induced pluripotent stem cell (hiPSC)-derived endothelial cells (hiPSC-ECs) provide a novel source of patient-specific cells and tissues for disease modeling, drug discovery, and regenerative therapeutics. Here we report the use of hiPSC-ECs to elucidate the role of miR-451a and let-7i-5p-loaded extracellular vesicles (EVs, such as exosomes) in the inflammatory response to free-heme as a model for heme-induced inflammation. We provide evidence of a significant correlation between miR-451a and let-7i-5p-loaded circulating exosomes in plasmodium-infected patients with reported clinical benchmarks of malaria-severity (e.g., Hemoglobin (Hb) levels, white blood cell counts). Additionally, we determined that exposure of Plasmodium falciparum (Pf) parasites to EVs, loaded with either miRNA, significantly reduces their counts in vitro. Using hiPSCs derived from individuals with wild-type Hb (HbAA) or homozygous sickle cell mutated Hb (HbSS) genotypes, we demonstrate that heme-treated hiPSC-ECs secreted inflammatory products (cytokines, chemokines and growth factors) into supporting media at concentrations that were similar to that reported in HbAA and HbSS serum. This inflammatory response was attenuated by exposure with miR-451a or let-7i-5p-loaded EVs. We also found a decrease in transcription of ICAM1 and P-Selectin, as well as the secretion of key inflammatory cytokines (e.g., CXCL10, TNF-α, and IFN-γ). Based on these findings, we propose a model in which increased levels of exosomal miR-451a and let-7i-5p in Plasmodium-infected individuals will attenuate inflammatory responses to free-heme and parasite-derived products. As a result, infected erythrocytes will less likely adhere to the endothelium, sequester in brain micro vessels, and reduce vaso-occlusive crises that exacerbate cerebral malaria.